THE RELATIONSHIP BETWEEN LACTATION COUNSELING AND INCREASING MOTHERS' KNOWLEDGE ABOUT EXCLUSIVE BREASTFEEDING - Tuti Ronista Bawamenewi; Elv.Feedia Mona Saragih; Wartaria Gulo; Widya Azzahra (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Background:Exclusive breastfeeding refers to giving only breast milk without additional fluids, including water, during the period of 0-6 months (Siahaan, 2021). The benefits of exclusive breastfeeding for newborns are very important as a preventive measure against infectious diseases, malnutrition, and death in infants and toddlers (Sabriana et al., 2022). One of the factors that impacts the behavior of exclusive breastfeeding is insight, which can trigger someone to give exclusive breastfeeding to their child. One of the methods applied is lactation preparation counseling for pregnant women to gain deeper insight into the emotional and physiological aspects of breastfeeding and to learn practical strategies and techniques in overcoming common challenges. Objective: To determine whether there is a relationship between lactation counseling and increasing maternal insight into exclusive breastfeeding, in order to provide better insight into the importance of support in breastfeeding and encourage optimal breastfeeding practices at the Hadijah Inpatient Pratama Clinic. Method: This research uses a quantitative research type with a pre-experimental research framework with a one group pre-test-post-test design method. The population includes all pregnant women in the third trimester, totaling 45 people. The sampling technique used Non Probability Sampling with Purposive Sampling type. Results: From the results of the Wilcoxon test, the P score was obtained with a value of 0.00 which means p <0.05 so that it was concluded that Ho was rejected Ha was approved which means there is an impact of lactation counseling on increasing maternal insight regarding exclusive breastfeeding.